2006
DOI: 10.1562/2005-12-10-ra-749
|View full text |Cite
|
Sign up to set email alerts
|

Two Native Pools of Phytochrome A in Monocots: Evidence from Fluorescence Investigations of Phytochrome Mutants of Rice

Abstract: Fluorescence investigations of phytochrome (phy) in rice (Oryza sativa L. cv. Nipponbare) mutants deficient in phyA, phyB and phyA plus phyB were performed. Total content of the pigment (P(tot)) and its spectroscopic and photochemical characteristics were determined in different parts of the dark-grown and far-red light (FR)-grown coleoptiles. Spectroscopically, phyA in the phyB mutant was identical to phyA in the wild-type (WT) and the extent of the conversion from Pr to lumi-R at 85 K was the same for phyA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
4
14
1
Order By: Relevance
“…the C3 1 atom consists of a mixture of ( R )‐ and ( S )‐diastereomers as well as the alternative side‐chain conformations adopted by the two methionines, M174 and M269. The possibility that two isoforms exist is consistent with numerous spectroscopic studies over the past 15 years for both plant and Cph1 phytochromes and also noted in the more primitive bacteriophytochromes . There is no evidence that these two isoforms result from preparation artifacts , but even if it were to be the case, still the fact would remain that one state, Pr, tends to exist in two isoforms, whereas the other, Pfr, is structurally homogenous.…”
Section: Mas Nmr Studies On Canonical Phytochromessupporting
confidence: 80%
“…the C3 1 atom consists of a mixture of ( R )‐ and ( S )‐diastereomers as well as the alternative side‐chain conformations adopted by the two methionines, M174 and M269. The possibility that two isoforms exist is consistent with numerous spectroscopic studies over the past 15 years for both plant and Cph1 phytochromes and also noted in the more primitive bacteriophytochromes . There is no evidence that these two isoforms result from preparation artifacts , but even if it were to be the case, still the fact would remain that one state, Pr, tends to exist in two isoforms, whereas the other, Pfr, is structurally homogenous.…”
Section: Mas Nmr Studies On Canonical Phytochromessupporting
confidence: 80%
“…Schmidt et al showed the existence of an isosbestic point between the main absorption peak and the shoulder upon temperature change in oat phytochrome (33). These findings were in contrast to a single electronic transition and were interpreted as heterogeneity of the Pr form as reported by Sineshchekov et al (14). Single molecule fluorescence studies on native Agp1 bacteriophytochrome showed clear evidence for heterogeneity at very low temperatures (13).…”
Section: Discussionmentioning
confidence: 84%
“…Heterogeneity of the chromophore ground state geometry can induce a broadening of absorption lines in the visible absorption spectrum and new, to our knowledge, spectral features in the vibrational pattern due to diverse interactions between the chromophore and the protein binding pocket, e.g., hydrogen bonds (11). For the Pr form, it is still under debate as of this writing whether the shoulder in the absorption spectrum around 620 nm and the biexponential decay with time constants of~3 ps and 30 ps of the isomerization dynamics originate from heterogeneity of the chromophore (12)(13)(14). With our method we are able to identify chromophore heterogeneity and separate contributions from different electronic transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The major ones are light-labile phytochrome A (phyA) and light-stable phytochrome B (phyB). phyA mediates all the types of the photoresponses-VLFR, HIR, and also LFR [17][18][19][20][21][22][23][24]. phyB is capable of mediating only the inductive LFR type.…”
Section: Introductionmentioning
confidence: 99%